DEVELOPMENT OF A SECURITY PROGRAM FOR PLACING LOADS ON VEHICLES OF TRANSPORTATION - A. Erkinjonov; O. Rakhmonov; SH.Chorshanbiev. (International Journal of Innovations in Engineering Research and Technology, 2023)
Nowadays, in order to safely deliver the goods to their owner, to reduce the impact of the loads on the stability of cars during the movement of the car, the loads are attached with special strap protection devices [1]. During the movement of the cargo placed on the platform of the transport vehicles, the center of gravity of the cargo moves from its place to a certain place, if errors are made in the placement and attachment of the cargo, it is inevitable that a road traffic accident will occur during transportation [2,3]. Theoretically, it is necessary to deal with reasons related to safe loading and attachment when finalizing the shipment process. It is necessary to take into account the technical capabilities of the car when carrying out the transportation of goods by means of transport, safe and high-quality transportation.